INVESTIGATING UNIVERSITY STUDENTS' MOTIVATIONAL ORIENTATION TOWARDS ENGLISH LANGUAGE LEARNING - Yuwita, Mia Rahmawati (Program Studi Sastra Inggris, Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2023)
This current study examines university students’ motivational orientations towards English language learning. This study conducts a semi-structured interview to gain rich data. To achieve the objective successfully, 6 students who take an English language major at a university in Bandung, Indonesia were interviewed to provide answers related to English language learning motivation. The results of this study have demonstrated the participants’ positive motivations towards English language learning. Through data analysis, the respondents positively express their strong motivations towards English language learning as they have a personal interest in English, the international language. Mastering English could help them adapt to this globalization era, and the status of English is essential as its use is immensely wide in many sectors. Yet, they understand that the status of Bahasa Indonesia and maintaining it are also crucial to their identity. Keywords: English language learning, English, Motivational orientation